Marketing Death: Culture and the Making of a Life Insurance Market in China - Lacbawan Jr., Macario B. (Kasarinlan: Philippine Journal of Third World Studies, 2015)
Review of Marketing Death: Culture and the Making of a Life Insurance Market in China by Cheris Shun-ching Chan (Oxford, UK: Oxford University Press)